PENGARUH INDEPENDENSI DEWAN KOMISARIS DAN INDEPENDENSI DEWAN DIREKSI TERHADAP STRUKTUR MODAL PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Witya Shalini; Elcy Handayani Pramita; Mila Asmawiani Okta; Galeh Sari (SUAN PUBLISHER, 2025)
This study aims to analyze the effect of board of commissioner independence and board of directors independence on capital structure. This study is a causal research. The data used in this study are secondary data. This research was conducted on Property & Real Estate companies listed on the Indonesia Stock Exchange in 2019-2023. The population in this study were all property & real estate companies listed on the IDX in 2019 to 2023. The number of samples selected according to the criteria set using purposive sampling techniques consisted of 12 companies covering the period 2019-2023, with a total observation of 60 companies. The data analysis method used in this study is the panel data regression analysis method and the moderating test which in this study uses the help of SPSS software. The results of this study indicate that board of commissioner independence and board of directors independence have a positive effect on company structure partially and simultaneously